A SECURE APPROACH TO FINANCIAL DOCUMENT AUTHENTICATION USING SECURE HASH ALGORITHM – 256 - Prasetya, Adityan Wisnu Yuda (Universitas Ahmad Dahlan, 2025)
The advancement of technology is currently accelerating. Many financial transactions are now completed online in digital format. Financial statements, audits, and other important financial documents are stored and shared online. In this situation, financial record security is critical, particularly in preventing document alteration or forgery. Some examples of financial document breaches in 2022 include BI, PTC, PLN, JMTO, and others. Financial document authentication procedures must be implemented to ensure their integrity and validity. Coding is a subset of mathematics that is used in the workplace, such as the Secure Hash Algorithm - 256 (SHA-256). It has several advantages that are far superior to others. To improve the security and trustworthiness of electronic financial documents, this study will use the SHA-256 authentication algorithm to ensure that no financial data is leaked to parties who should not receive it.